Synthesis and Experimental Validation of New PDI Inhibitors with Antiproliferative Activity - Mariateresa Badolato; Gabriele Carullo; Francesca Aiello; Antonio Garofalo (Journal of Chemistry)
Protein disulfide isomerase (PDI) is a member of the thioredoxin superfamily of redox enzymes. PDI is a multifunctional protein that catalyzes disulfide bond formation, cleavage, and rearrangement in unfolded or misfolded proteins and functions as a chaperone in the endoplasmic reticulum. Besides acting as a protein folding catalyst, several evidences have suggested that PDI can bind small molecules containing, for example, a phenolic structure, which includes the estrogenic one. Increasing studies indicate that PDI is involved in both physiology and pathophysiology of cells and tissues and is involved in the survival and proliferation of different cancers. Propionic acid carbamoyl methyl amides (PACMAs) showed anticancer activity in human ovarian cancer, both in vitro and in vivo, by inhibiting PDI. The inhibition of PDI’s activity may have a therapeutic role, in various diseases, including cancer. In the present study, we designed and synthesized a diversified small library of compounds with the aim of identifying a new class of PDI inhibitors. Most of synthesized compounds showed a good inhibitory potency against PDI and particularly 4-methyl substituted 2,6-di-tert-butylphenol derivatives (8–10) presented an antiproliferative activity in a wide panel of human cancer cell lines, including ovarian ones.